IMPLEMENTATION THE PEDAGOGICAL CONTENT KNOWLEDGE (PCK) OF PHYSIC TEACHER BASED-ON STUDENTS LEARNING OUTCOMES AT SMAN 4 BANDA ACEH - Saminan, Saminan; Zulfira, Roza (SCAD Independent, 2016)
One of the factors of low student learning outcomes on physic learning coursed lack of ability teachers in effecting the pedagogic practice and knowing subject matter in the learning environment. Pedagogical content knowledge (PCK) is the blending of pedagogical knowledge and content knowledge which must have by teachers in realizing learning objectives. This research aims to showed the implementation pedagogical content knowledge (PCK) of physic teacher based on students learning outcomes on measurement and magnitude material at class of X IA4 SMAN 4 Banda Aceh. Outcomes of this research are: the average value of students learning outcomes is 80 with description the PCK of physic teacher are 95% teacher have understood students of characteristics in learning process, 67% teacher success in planning of learning, 70% teacher success in implementing learning activities, 67% teacher success in evaluating learning outcomes, 75% teacher has been able developing the potentials of the students, and 75% teacher has mastered the science of substances.